Impact of pollutant emission reductions on summertime aerosol feedbacks: A case study over the PO valley. (December 2015) - Carnevale, C.; Finzi, G.; Pederzoli, A.; Turrini, E.; Volta, M.; Ferrari, F.; Gianfreda, R.; Maffeis, G.
Abstract: This study presents an evaluation of the impact by future pollutant anthropogenic emission reductions on summertime aerosol feedbacks over the Po valley. The fully coupled on line model Wrf/Chem has been used to examine the air quality and meteorology response over the region to 2020 emission reductions with respect to a simulation base case (2013). Future changes in net short wave radiation flux (SW) are also analyzed. The model domain is a 6 × 6 km 2 resolution grid over Northern Italy; the simulation period covers two summer months (July–August). The work is divided into two parts. In the first, model results for the Base Case simulation (BC) are evaluated by comparing Wrf/Chem output to surface observations provided by two monitoring networks. Approximately 25 sites belonging to the regional ARPA Lombardia Network are used for both chemistry (NO2, O3 and PM10 concentrations) and meteorology (wind speed and 2-meters temperature) evaluation; 4 stations part of the global AEROsol Robotic Network (AERONET) are used for the evaluation of Aerosol Optical Depth (AOD). In the second part, a Maximum Feasible Reduction (MFR) scenario at 2020 have been simulated for the same months; monthly direct, indirect and overall aerosols feedbacks for both BC and MFR have been computed and analyzed. The emission reductions in the MFR 2020 lead to a sensible change in the aerosol overall feedbacks for all variables; a drop of SW over the valley (cooling effect) is visible in both BC and MFR, but it is less significant in the MFR (−5 W m −2 ) compared to the BC (−45 W m −2 ). This difference is mainly due to the abatement of SO2 primary emissions, which leads to lower sulfates concentrations scattering radiation, thus mitigates the cooling effect and favors the warming. As SW is higher in the MFR, T2 also increases over land with respect to the BC (the cooling of −0.5 °C estimated in the Base Case almost disappears). The overall effects lead to an enhancement of PM10 concentration in the BC; they are less efficient in the MFR because of lower secondary aerosol concentrations (associated to the reduction of primary PM10 emissions by approximately 20%). Concerning NO2, some localized areas with high reductions in the BC are not visible in the MFR. This is consistent with the increase of T2, which leads to higher photolytic rates compared to the BC. Higher concentrations of NO2 in the MFR with respect to the BC lead to lower O3 concentrations (maximum O3 values drop from +6 ppb to +3 ppb). Highlights: The fully coupled on line model Wrf/Chem has been used over the Po valley region. The study focuses on future aerosol feedbacks over the Po valley. Future changes in air quality and meteorology are analyzed.